2022
DOI: 10.1002/ctm2.730
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the transcriptional heterogeneity of organ‐specific metastasis in human gastric cancer using single‐cell RNA Sequencing

Abstract: Background Deciphering intra‐ and inter‐tumoural heterogeneity is essential for understanding the biology of gastric cancer (GC) and its metastasis and identifying effective therapeutic targets. However, the characteristics of different organ‐tropism metastases of GC are largely unknown. Methods Ten fresh human tissue samples from six patients, including primary tumour and adjacent non‐tumoural samples and six metastases from different organs or tissues (liver, peritoneum, ovary, lymph node) were evaluated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 133 publications
(287 reference statements)
2
78
0
Order By: Relevance
“…Similarly, a large number of Tregs showed infiltration into the tumor tissue compared to the adjacent tissue. Along with all these findings, Jiang et al (2022) and Kumar et al (2022) confirmed that with tumor progression the tissue microenvironment changes from predominance of proinflammatory effectors to predominance of immunosuppressive Tregs (34,35). Qu et al (2022) identified a distinct Treg phenotype that is increased in tumor tissue compared to patientmatched blood and defined by enriched expression of the TNF receptor superfamily member 1B (TNFR2) (30).…”
Section: T Cellsmentioning
confidence: 82%
See 4 more Smart Citations
“…Similarly, a large number of Tregs showed infiltration into the tumor tissue compared to the adjacent tissue. Along with all these findings, Jiang et al (2022) and Kumar et al (2022) confirmed that with tumor progression the tissue microenvironment changes from predominance of proinflammatory effectors to predominance of immunosuppressive Tregs (34,35). Qu et al (2022) identified a distinct Treg phenotype that is increased in tumor tissue compared to patientmatched blood and defined by enriched expression of the TNF receptor superfamily member 1B (TNFR2) (30).…”
Section: T Cellsmentioning
confidence: 82%
“…This is because DCs are not always identified within the datasets, and if they are, they are generally represented at a low frequency. Jiang et al (2022) found the greatest population of DCs in metastatic lymph node derived tissue compared to primary tumor tissue (34). This is unsurprising since DCs typically reside in high frequency in the lymph node.…”
Section: Myeloid Cellsmentioning
confidence: 98%
See 3 more Smart Citations